Gut Microbiota Modification: Another Piece in the Puzzle of the Benefits of Physical Exercise in Health? - Cerdá, Begoña; Pérez, Margarita; Pérez-Santiago, Jennifer D.; Tornero-Aguilera, Jose F.; González-Soltero, Rocío; Larrosa, Mar (Frontiers in Physiology, 2016)
Regular physical exercise provides many health benefits, protecting against the development of chronic diseases, and improving quality of life. Some of the mechanisms by which exercise provides these effects are the promotion of an anti-inflammatory state, reinforcement of the neuromuscular function, and activation of the hypothalamic–pituitary–adrenal axis. Recently, it has been proposed that physical exercise is able to modify gut microbiota, and thus this could be another factor by which exercise promotes well-being, since gut microbiota appears to be closely related to health and disease. The purpose of this paper is to review the recent findings on gut microbiota modification by exercise, proposing several mechanisms by which physical exercise might cause changes in gut microbiota.